Distribution of Inorganic and Total Mercury in Marine Sediments from Two Coastal Areas Delimited by Atlantic Ocean: Galician Rías (NW Spain) and Coast of Dakar (Senegal) - Ndiaye, Birame; Ndiaye, Momar; Pérez Cid, Benita; Diop, Abdoulaye (Asian Journal of Chemistry, 2015)
Surface marine sediments proceeding from two Galician Rías (NW Spain) and the coast of Dakar (Senegal) were analyzed by cold vapor atomic absorption spectrometry (CV-AAS) in order to evaluate the distribution of inorganic and total mercury as well as to compare the pollution levels in both aquatic systems. The accumulation of mercury in Galician sediments (values < 0.12 μg/g) was considerably higher than that found in sediments from the Dakar coast (values < 0.025 μg/g). Nevertheless, all the samples studied can be considered unpolluted on mercury according to the quality criteria (values < 0.05 μg/g) used for the classification of sediments. A similar distribution was observed for inorganic and total mercury, with ratios inorganic mercury/total mercury ranging from 97.1 to 99.8 %, indicates that inorganic mercury is the main specie of mercury in all samples studied. Two latent variables, explaining the 99.11 % of the initial variance, were extracted from the data using principal component analysis. This allowed sediments to be grouped in two different subgroups according to their similar behaviour.